2004
DOI: 10.1126/science.1102374
|View full text |Cite
|
Sign up to set email alerts
|

arrA Is a Reliable Marker for As(V) Respiration

Abstract: Arsenate [As(V)]-respiring bacteria affect the speciation and mobilization of arsenic in the environment. This can lead to arsenic contamination of drinking water supplies and deleterious consequences for human health. Using molecular genetics, we show that the functional gene for As(V) respiration, arrA, is highly conserved; that it is required for As(V) reduction to arsenite when arsenic is sorbed onto iron minerals; and that it can be used to identify the presence and activity of As(V)-respiring bacteria in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
177
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(187 citation statements)
references
References 6 publications
7
177
1
1
Order By: Relevance
“…As(III) methylation genes (arsM) constituted secondary important part of total As metabolism genes (6e9%) among all five paddy soils, and higher than aio and arr in our samples, implying a strong potential to produce methylated As species, which could be uptake by rice roots and explain why most rice contains unusually high concentrations of methylated As species compared with other cereals (Jia et al, 2013). The low abundance of arr genes compared with the others detected in the five paddy soils, which has also been confirmed either in paddy soils or As and antimony (Sb) contaminated mine field (Jia et al, 2014(Jia et al, , 2013Luo et al, 2014;Zhang et al, 2015), could be partly ascribed to their specific presence in anaerobic As(V) respiring bacteria (Malasarn et al, 2004;Silver and Phung, 2005). Previous studies showed that total As concentrations in paddy soils correlated positively with the abundance of genes involved in As biotransformation processes (Zhang et al, 2015), and concentrations of different As species in soil solutions have also been revealed good correlations with the abundance of genes responsible for different As biotransformation processes in microcosm experiments (Jia et al, 2014(Jia et al, , 2013.…”
Section: Abundance Of As Metabolism Genes and Statistical Analysismentioning
confidence: 68%
See 3 more Smart Citations
“…As(III) methylation genes (arsM) constituted secondary important part of total As metabolism genes (6e9%) among all five paddy soils, and higher than aio and arr in our samples, implying a strong potential to produce methylated As species, which could be uptake by rice roots and explain why most rice contains unusually high concentrations of methylated As species compared with other cereals (Jia et al, 2013). The low abundance of arr genes compared with the others detected in the five paddy soils, which has also been confirmed either in paddy soils or As and antimony (Sb) contaminated mine field (Jia et al, 2014(Jia et al, , 2013Luo et al, 2014;Zhang et al, 2015), could be partly ascribed to their specific presence in anaerobic As(V) respiring bacteria (Malasarn et al, 2004;Silver and Phung, 2005). Previous studies showed that total As concentrations in paddy soils correlated positively with the abundance of genes involved in As biotransformation processes (Zhang et al, 2015), and concentrations of different As species in soil solutions have also been revealed good correlations with the abundance of genes responsible for different As biotransformation processes in microcosm experiments (Jia et al, 2014(Jia et al, , 2013.…”
Section: Abundance Of As Metabolism Genes and Statistical Analysismentioning
confidence: 68%
“…Distribution, diversity, and abundance of aioA and arrA genes To investigate the potential As redox in the environment, aioA has been proposed as a valuable functional marker gene responsible for As(III) oxidation and arrA as a reliable marker gene for As(V) respiration reduction (Malasarn et al, 2004;Qu em eneur et al, 2008;Silver and Phung, 2005). AioA and ArrA proteins are both molybdenum-containing enzymes in the dimethyl sulfoxide (DMSO) reductase family (Oremland and Stolz, 2005;Silver and Phung, 2005), sharing similar amino acid length and structural characteristic while carrying out completely distinct functions.…”
Section: Abundance Of As Metabolism Genes and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Arsenate, anthraquinone 2,6-disulfonate (AQDS), elemental sulfur, ferric citrate, ferric oxyhydroxide, manganese, nitrate, nitrite, nickel, molecular oxygen and selenium were not utilized as terminal electron acceptors. The inability of strain JW/ YJL-B18 T to reduce arsenate was further suggested by the failure to obtain a PCR product for the arsenate reductase gene (arrA) (Malasarn et al, 2004). Several other morphological and physiological characters separate the novel isolate from other Desulfosporosinus species (Table 1).…”
mentioning
confidence: 99%